Paradigm shift to Quadruple Helix Model of Innovation in Malaysia - Thanaletchumy Krishnan,; Nur Riza Mohd Suradi,; Faridatulazna Ahmad Shahabuddin, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Innovation is crucial for sustainable economic growth, development, and national prosperity. A progressive and sustainable innovation ecosystem is required to achieve a high-income, developed, and high-technology nation status as well as to be a globally competitive nation. For this reason, the quadruple helix innovation model (QHIM) plays a significant role in economic growth and national development driven by science, technology, and innovation (STI). Collaboration and commitment among the four helices are essential for Malaysia to achieve National Transformation 2050 (TN50), Industrial Revolution 4.0 (IR4.0), Shared Property Vision (WKB 2030) and Agenda 2030. This paper reviews innovation collaboration in Malaysia focusing on QHIM. This paper concludes that Malaysia highly requires quadruple helix collaboration to be a developed and high-income nation. Malaysia's economic growth and national development depend on the implementation of the QHIM where the four helices integrate and collaborate to achieve sustainable wealth and prosperity through innovation.